Thinking about biology - Webster, Stephen (Cambridge University Press, 2003)
Intended for biology students, this philosophical commentary on biology makes science students' studies more interesting by offering an easy way of studying the philosophy of science, as well as engaging in debates about the social and political implications of biology. It is a unique biology textbook because it adopts an explicitly philosophical approach.